Major nutrient requirement of mango-ginger (Curcuma amada Roxb.) - JAYACHANDRAN, K R MRIDULA, B K (Journal of Spices and Aromatic Crops, 1999)
Field trials conducted at Vellayani (Kerala, India) with factorial combinations of three levels each of nitrogen (15, 30 and 45 kg N ha-1), phosphorus (15, 30 and 45 kg P20 5 ha-1) and potassium (30, 60 and 90 kg K2O ha-1) revealed that N, P,05 and K2O @ 30 : 30 : .60 kg ha-1 was optimum for obtaining maximum net returns and benefit-cost ratio in mango-ginger (Curcuma amada).